A Wireless Sensor Network‐Based Structural Health Monitoring System for Highway Bridges. (17th August 2012) - Hu, Xiaoya; Wang, Bingwen; Ji, Han
<x xml:space="preserve">Abstract</x> Abstract: An integrated structural health monitoring (SHM) system for highway bridges is presented. The system is based on a customized wireless sensor network platform with a flexible design that provides a variety of sensors typical in SHM. These sensors include accelerometers, strain gauges, and temperature sensors with ultra‐low power consumption. An S‐Mote node, an acceleration sensor board, and a strain sensor board are developed to satisfy the requirements of bridge structural monitoring. Communication software components are integrated within TinyOS operating system to provide a flexible software platform whereas the data processing software performs analysis of acceleration, dynamic displacement, and dynamic strain data. The prototype system comprises a nearly linear multi‐hop topology and is deployed on an in‐service highway bridge. Data acquired from the system are used to examine network performance and to help evaluate the state of the bridge. Experimental results show that the system enables continuous or regular interval monitoring for in‐service highway bridges.